Asymptotic behavior of the best approximations for the functions in L_p - Pichugov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The asymptotic behavior of the ratio E_n (f)_p/ω(f, α/ n)_p is studied for individual periodic functions f L_p.